A way to implement the electro-optical technique to inertial MEMS. Issue 9 (August 2015) - Melendez, K.; Desmoulin, A.; Sanchez, K.; Perdu, P.; Lewis, D.
Abstract: This paper describes a new way to analyze inertial MEMS with the electro-optical technique. Usually, this technique is used in failure analysis to probe on electronic devices from old technologies to modern VLSI. In our case, we make use of the variation in power of the reflected beam between different layers of materials in an accelerometer (MEMS). We introduce a new method based on the electro-optical technique to extract a physical resonant frequency in inertial MEMS.